The Hedgehog Pathway Conditions the Bone Microenvironment for Osteolytic Metastasis of Breast Cancer. (1st December 2011) - Das Das, Shamik Shamik; Samant Samant, Rajeev S. Rajeev S.; Shevde Shevde, Lalita A. Lalita A.
Abstract : The microenvironment at the site of tumor metastasis plays a key role in determining the fate of the metastasizing tumor cells. This ultimately has a direct impact on the progression of cancer. Bone is the preferred site of metastasis of breast cancer. Painful, debilitating osteolytic lesions are formed as a result of crosstalk between breast cancer cells and cells in the bone, predominantly the osteoblasts and osteoclasts. In this paper, we have discussed the temporal and spatial role of hedgehog (Hh) signaling in influencing the fate of metastatic breast cancer cells in bone. By virtue of its secreted ligands, the Hh pathway is capable of homotypic and heterotypic signaling and consequently altering the microenvironment in the bone. We also have put into perspective the therapeutic implications of using Hh inhibitors to prevent and/or treat bone metastases of breast cancer.